1994
DOI: 10.1200/jco.1994.12.5.1005
|View full text |Cite
|
Sign up to set email alerts
|

Sequential prophylactic oral and empiric once-daily parenteral antibiotics for neutropenia and fever after high-dose chemotherapy and autologous bone marrow support.

Abstract: The therapeutic strategy of ciprofloxacin and rifampin followed by once-daily vancomycin and tobramycin markedly reduced the incidence of infection and virtually eliminated bacteremia in both purged and nonpurged bone marrow recipients. Once-daily vancomycin and tobramycin was safe and effective and, because of the ease of use, facilitates outpatient management of ABMT patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
2
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 17 publications
5
41
2
3
Order By: Relevance
“…7,8 However, they are in contrast to many investigators who have reported up to 100% incidence of febrile neutropenia in this patient population, 3,9-14 and Mossad et al 2 and Shea et al 15 who reported a lower incidence. This might be due to different criteria for patient selection and indications to start antimicrobial therapy.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…7,8 However, they are in contrast to many investigators who have reported up to 100% incidence of febrile neutropenia in this patient population, 3,9-14 and Mossad et al 2 and Shea et al 15 who reported a lower incidence. This might be due to different criteria for patient selection and indications to start antimicrobial therapy.…”
Section: Discussioncontrasting
confidence: 50%
“…Antifungal prophylaxis has not been shown to be useful for patients with short periods of neutropenia after PBSCT. Gilbert et al 8 reported a fungemia rate of about 4%, and no patient affected had received antifungal prophylaxis. In our own study, only one patient not taking antifungal prophylaxis developed a fungemia caused by Candida glabrata, a fungal pathogen known to be potentially resistant to azole antifungals.…”
Section: Discussionmentioning
confidence: 99%
“…17 The addition of erythromycin to ciprofloxacin prophylaxis failed to be of any benefit following transplantation in one study. 18 However, the use of alternative agents with activity against gram-positive organisms such as oral roxithromycin, 19,20 intravenous penicillin, 21 intravenous cephalothin, 19 oral amoxicillin, 22 oral rifampicin 23 and intravenous vancomycin 24 have all significantly reduced the incidence of viridans streptococcal bacteremia. Viridans streptococcal bacteremia was observed in 17.5% of our patients undergoing autologous PBSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Since the early 1990s, there have been several published reports of successful outpatient-based autologous HSCT. [7][8][9][10][11][12][13][14][15] The experience with outpatient management of allogeneic HSCT has been quite limited outside the context of nonmyeloablative HSCT. [16][17][18] The group at John Hopkins reported on an in-patient-outpatient continuumof-care model for both autologous and allogeneic HSCT that resulted in a substantial cost savings, particularly in patients with standard risk disease, without an increase in clinical complications.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have shown that autologous HSCT can be safely delivered in the outpatient setting with good outcomes and diminished cost. [7][8][9][10][11][12][13][14][15] In addition, allogeneic transplantation after nonmyeloablative conditioning also seems feasible in the ambulatory care setting, [16][17][18] given its significantly reduced regimen-related toxicities compared with standard allogeneic HSCT. A few pilot studies have explored the safety of outpatient myeloablative allogeneic HSCT 4,19 in small numbers of selected patients, but none have documented whether this approach is generalizable to the majority of patients requiring such therapy.…”
Section: Introductionmentioning
confidence: 99%